Two Places for Causees in Productive IsiXhosa Morphological Causatives. (11th March 2021) - Myler, Neil; Mali, Zoliswa O.
Abstract: Productive morphological causatives in isiXhosa exhibit a case alternation with respect to the causee: it can be unmarked or instrumental. Much recent literature on similar alternations in causative constructions in other languages analyzes them as involving differences in the size or category of the constituent selected by the causative morpheme. We show that such an analysis cannot be extended to isiXhosa and that both alternants are verb‐selecting causatives. We propose instead that the alternation actually concerns the place in the structure in which the causee is introduced: in the specifier of the causative head itself in the unmarked‐causee construction, in a PP adjoined to the embedded verb phrase in the instrumental‐causee construction. This article thus adds to a growing body of evidence that the same thematic roles are not always assigned in the same syntactic positions.